Toefl grammar guide book for beginners 2 / Silvester Goridus Sukur ; penyunting, Aprina Tri Retnaningrum - SILVESTER GORIDUS SUKUR; Aprina Tri Retnaningrum (Indonesia Cerdas, 2016)
467 hlm. : ilus. ; 26 cm